Sidewalk accessibility at Melaka’s traditional streets for people with disabilities (PWDS) - Ja'afar, Nor Haslina; Abdul Rahim, Asiah; Abd Samad, Nur Amirah; Che Rahim, Che Raiskandar (2016)
The accessibility of street as a social arena that fulfills the need for people with disabilities (PwDs) is essential in the urban design field especially traditional street as a public space. In contrast, the accessibility in traditional streets area is still lacking especially for PwDs. Aims: The purpose of this paper is to determine the level of accessibility for PwDs of the sidewalk component in a traditional street design by referring to the minimum design requirements provided in Malaysian Standards, MS1184:2014. Method: Qualitative approach is applied in this study and involves conducting an access audit where the data will be analyzed concurrently with descriptive qualitative by thematic analysis. Jalan Hang Jebat (Jonker Walk) that represent one of the traditional streets in the Melaka Historical City, Malaysia was selected as a case study because it is one of the famous places in attracting people from different background, which should be accessible for all as a UNESCO tourist attraction street. Result: The access audit discovers that in designing traditional streets as public space that is accessible for PwDs, the approach of street design is crucial in order to determine the function of the existing sidewalk and how to make a more accessible approach. Outcome: This study is expected to be useful for architect, city planners and urban designer as a future reference in designing or retrofitting traditional street as an accessible public space.